PHASE CONTRAST AND INTERFEROMETRIC MICROSCOPY OF THE L.E. CELL PHENOMENON - Rifkind, Richard A. (The Rockefeller University Press, 1957)
Alterations in the cellular morphology of polymorphonuclear leukocytes and lymphocytes under the influence of serum from patients having disseminated lupus erythematosus were observed under the phase contrast microscope. These changes appear to involve the cell nucleus without significant visible incorporation of cytoplasm. In the formation of the L.E. body, there is a loss of internal nuclear structure and a subsequent nuclear swelling and extrusion of the nuclear contents from the cell to form the free L.E. body. The possible incorporation of cytoplasmic substance cannot alone account for the large mass of the L.E. body as contrasted with the parent nucleus or nuclear lobe. Measurements of dry mass by means of the interference microscope show a two and one-half-fold increment in dry mass in L.E. bodies compared to parent lymphocyte nuclei. This confirms previous cytochemical studies, and establishes that an influx of protein into the leukocyte nucleus is an integral part of the L.E. phenomenon. That the accumulation of extraneous protein within the L.E. body is simultaneous with or subsequent to a disruption of the normal structure of the leukocyte nucleus is apparent from these studies, but the pathogenesis of this alteration is as yet unknown.